Evaluation of the sensitivity of two 3D diode array dosimetry systems to setup error for quality assurance (QA) of volumetric‐modulated arc therapy (VMAT). (6th September 2013) - Li, Guangjun; Bai, Sen; Chen, Nianyong; Henderson, Lansdale; Wu, Kui; Xiao, Jianghong; Zhang, Yingjie; Jiang, Qingfeng; Jiang, Xiaoqin
Abstract : The purpose of this study is to evaluate the sensitivities of 3D diode arrays to setup error for patient‐specific quality assurance (QA) of volumetric‐modulated arc therapy (VMAT). Translational setup errors of ± 1, ± 2, and ± 3 mm in the RL, SI, and AP directions and rotational setup errors of ± 1 ° and ± 2 ° in the pitch, roll, and yaw directions were set up in two phantom systems, ArcCHECK and Delta 4, with VMAT plans for 11 patients. Cone‐beam computed tomography (CBCT) followed by automatic correction using a HexaPOD 6D treatment couch ensured the position accuracy. Dose distributions of the two phantoms were compared in order to evaluate the agreement between calculated and measured values by using γ analysis with 3%/3 mm, 3%/2 mm, and 2%/2 mm criteria. To determine the impact on setup error for VMAT QA, we evaluated the sensitivity of results acquired by both 3D diode array systems to setup errors in translation and rotation. For the VMAT QA of all patients, the pass rate with the 3%/3 mm criteria exceeded 95% using either phantom. For setup errors of 3 mm and 2°, respectively, the pass rates with the 3%/3 mm criteria decreased by a maximum of 14.0% and 23.5% using ArcCHECK, and 14.4% and 5.0% using Delta 4 . Both systems are sensitive to setup error, and do not have mechanisms to account for setup errors in the software. The sensitivity of both VMAT QA systems was strongly dependent on the patient‐specific plan. The sensitivity of ArcCHECK to the rotational error was higher than that of Delta 4 . In order to achieve less than 3% mean pass rate reduction of VMAT plan QA with the 3%/3 mm criteria, a setup accuracy of 2 mm/1° and 2 mm/2° is required for ArcCheck and Delta 4 devices, respectively. The cumulative effect of the combined 2 mm translational and 1° rotational errors caused 3.8% and 2.4% mean pass rates reduction with 3%/3 mm criteria, respectively, for ArcCHECK and Delta 4 systems. For QA of VMAT plans for nasopharyngeal cancer (NPC) using the ArcCHECK system, the setup should be more accurate. PACS numbers: 87.55.ne, 87.55.Qr, 87.55.km